Stage III-B Cervical-cancer of Young Age in Medical, Bioethics and Clinical Ethics Perspectives (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The incidence of cervical-cancer in Indonesia is mostly obtained at the age of 40-50 years. But now many are found at the age of 25-40 years. Method: Case-report. Findings: Female, 25 years old with a diagnosis of cervical-cancer stage 3B planned for chemotherapy. Patients complain of vaginal bleeding. Married 2 times, at the age of 16 years and 19 years with infertility. The central dilemma: a young woman with advanced stage cervical-cancer was planned for chemotherapy as a gold standard, in terms of patient-autonomy and family refusal. Informed concent was required in the delivery of bad-news and human approaches based on Kubler-Ross’s theory (denial, anger, bargaining, depression, acceptance) with the concept of SPIKES (Settings, Listening-Skills, Patient’s Perception, Invitation to share Information, Knowledge transmission “bad-news”, Explore Emotions and Empathize, Summarize and Strategize). Both medical indication and quality of life were appropriated but in terms of patient preference and contextual feature were refused by patient and families. Resolving this case was not enough with medical-aspects, it also required a bioethical and clinical ethics approach. Conclusion: Medical, bioethical and clinical ethics approaches are methods of resolving a case with an ethical dilemma.